Transforming "sympathetic interlocutors" into veto players - Bernhard Reinsberg; Andreas Kern; Matthias Rau-Goehring (European Central Bank (ECB), 2021)
International organizations (IOs) often drive policy change in member countries. Given IOs' limited political leverage over a member country, previous research argues that IOs rely on a combination of hard pressures (i.e., conditionality) and soft pressures (i.e., socialization) to attain their political goals. Expanding this literature, we hypothesize that IOs can enhance their political leverage through loan conditions aimed at politically empowering 'sympathetic interlocutors'. Studying this mechanism in the context of the International Monetary Fund (IMF), we argue that through prescribing structural loan conditions on central banks (CBI conditionality), the IMF empowers monetary authorities that can serve as a veto player to the government. Relying on a dataset including up to 124 countries between 1980 and 2012, we find that the IMF's CBI conditionality correlates to countries with fewer checks and balances, a less independent central bank, and where the government relies more heavily on the monetization of public debt.
Keywords: E52; E58; F5; 330; Central bank independence; International Monetary Fund; conditionality; internationalpolitical economy